Partisipasi Masyarakat dalam Program Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat (PAMSIMAS) Tahun 2022 di Desa Batu Putih Kabupaten Konawe Selatan - La Ibal; Endang Abubakar (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Efforts to overcome the problem of the availability of clean water in Indonesia are by involving community participation in the planning, implementation and maintenance of clean water facilities and infrastructure in the community. This service aims to find out the form of community participation in supporting the clean water availability program in Batu Putih Village. The service uses a qualitative descriptive analysis. Forms of Community Participation in the PAMSIMAS Program in Batu Putih Village, East Kolono District, Konawe Selatan District are (1) Planning, forms of community participation appear in the planning, implementation and maintenance stages. In the planning stage, community participation in the PAMSIMAS Program is in the form of contributions; (2) Implementation, Pamsimas activities are carried out after the disbursement of funds, community participation is mutual cooperation when clearing land for the manufacture of clean water storage tanks; (3) Operational and Maintenance, community participation is to keep the Pamsimas infrastructure that has been built running well; and (4) Strengthening Sustainability, community participation is participating in bookkeeping training and training to repair damaged equipment and so on.